Kemitraan guru dan dosen dalam menjaga kualitas pembelajaran daring saat Pandemi Covid-19 menghasilkan artikel publikasi bersama - Suseno, Nyoto; Purwaningsih, Purwaningsih; Aththibby, Arif Rahman; Harjati, Purwiro; Wahono, Lakon (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
Online learning is an option in the COVID-19 pandemic situation. The purpose of the lecturer and teacher partnership program is to maintain the quality of learning in schools that are carried out online. In addition, this activity aims to improve the pedagogical competence of teachers and lecturers and produce scientific articles jointly prepared between teachers and lecturers for publication. This partnership activity consists of 3 stages: Phase 1, FGD to determine action plans and research lessons; Phase 2, Implementation of Lesson Study (Plan-Do-See); and Phase 3, research collaboration to produce joint scientific articles. This activity agreed that the research lesson studied was the application of Problem-Based Learning (PBL) and Project-Based Learning (PjBL) to develop 4Cs abilities. Lesson study activities produce learning program plan documents and learning videos. The results of the community service program through the partnership of FKIP UM Metro lecturers with SMA Negeri 1 Metro teachers can be concluded that: (1) Lecturer and teacher partnerships in Lesson Study activities can maintain the quality of online mode learning in the COVID-19 pandemic situation through the application of PBL and PjBL; (2) Lecturer and teacher partnerships through the concepts and principles of lesson study can improve the pedagogical competence of lecturers and teachers; (3) Collaborative collaboration between lecturers and teachers in action research can increase scientific publications and produce 3 article publications in several Sinta 3 & 4 journals. Other findings that can be put forward, namely: google classroom and google meet can be used to overcome online learning during the pandemic Covid-19, as well as the application of PBL and PjBL in online mode learning, is effective for developing 4Cs and learning outcomes